PENGARUH STRUKTUR MODAL, SIZE, DAN TANGIBILITY TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Gracia Jesslyn; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aimed to empirically identify the effect of capital structure, size and tangibility on firm performance of manufacturing industry listed in Indonesia Stock Exchange (IDX). This study used purposive sampling with a total sample of 75 manufacturing companies listed on Indonesia Stock Exchange over the period of 2016-2018. Data processing in this research used multiple regression analysis with the help of SPSS program (Statistical Product and Service Solution) and Microsoft Excel 2013. The results showed that STD / TA and LTD / TA had no effect on firm performance, TD / TA and tangibility had a negative effect on firm performance, while size had a positive effect on firm performance. The implication of this study is when manufacturing companies listed in the IDX has the right capital structure and asset management, then the firm performance can be improved.